2019
DOI: 10.1002/pds.4779
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second breast cancer events with chronic opioid use in breast cancer survivors

Abstract: Purpose Opioids may increase cancer risk and progression through multiple pathways. Our objective was to estimate the association between chronic opioid use and risk of second breast cancer events (SBCEs). Methods Cohort study of women greater than or equal to 18 years, diagnosed with early stage breast cancer between January 1, 1990, and December 31, 2008, and enrolled in a large health plan for 1+ years before and after (unless died) diagnosis. SBCEs were defined as evidence of recurrence or second primary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…A retrospective analysis found no correlation between the total amount of consumed opioids after curative lung cancer resection and long-term survival or recurrence rates [ 40 ]. Similar results were found in two large cohort studies on postoperative chronic opiate use after breast cancer surgery [ 41 , 42 ]. However, a further retrospective study of a single centre showed a significant reduction in overall survival.…”
Section: Pain Managementsupporting
confidence: 89%
“…A retrospective analysis found no correlation between the total amount of consumed opioids after curative lung cancer resection and long-term survival or recurrence rates [ 40 ]. Similar results were found in two large cohort studies on postoperative chronic opiate use after breast cancer surgery [ 41 , 42 ]. However, a further retrospective study of a single centre showed a significant reduction in overall survival.…”
Section: Pain Managementsupporting
confidence: 89%
“…The proportion of patients using opioids in the current study was higher than that reported in other studies in breast cancer survivors, which reported chronic opioid use ranging from 2% to 10%. These differences may have been, in part, related to the definitions of chronic opioid use used in those studies (continuous use for ≥75 to ≥90 days) relative to the definition in the current study (analgesic use ≥30 days) [27][28][29]. Among patients using opioid-containing oral analgesics in the current study, nearly three-quarters reported no laxative use despite treatment guidelines for both cancer and noncancer patients that recommend utilization of laxatives for the treatment and prevention of opioid-induced constipation (Pappagallo [20] and NCCN guidelines [21]), which would have been available at the time of ATAC.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies investigated opioid use among patients with various specific health conditions: 43 studies 24,26–28,31,37,43,48,49,51,52,59,62,65,70,74,77–80,82–104 focused on noncancer pain, 14 studies 55,56,64,69,105–114 on musculoskeletal conditions, 13 studies 38–40,57,81,115–122 on injuries or trauma and eight studies 23,32,53,67,75,123–125 on infectious diseases. Seven studies 41,44,45,71,126–128 included patients with both cancer and noncancer pain, and six studies evaluated patients with cancer 60,129,130 or cancer survivors 61,131,132 . (Table 1)…”
Section: Resultsmentioning
confidence: 99%
“…LTOT definitions were based on previous publications (81 studies, 63%), clinical judgment (21 studies, 16%) or empirical data (four studies, 3%) (see Table 2), and only 13 studies 34,51,58,60,63,66,79,80,92,97,132,138,139 tested more than one definition (10%).…”
Section: Resultsmentioning
confidence: 99%